A recombinant vaccine of Riemerella anatipestifer OmpA fused with duck IgY Fc and Schisandra chinensis polysaccharide adjuvant enhance protective immune response. (November 2019) - Yang, Shifa; Dong, Wenwen; Li, Guiming; Zhao, Zengcheng; Song, Minxun; Huang, Zhongli; Fu, Jian; Jia, Fengjuan; Lin, Shuqian
Abstract: Riemerella anatipestifer ( R. anatipestifer ) causes septicemia and infectious serositis in domestic ducks, leading to high mortality and great economic losses worldwide. Vaccination is currently considered the best strategy to prevent R. anatipestifer infection in ducklings. In this study, we fused the duck IgY Fc gene to the outer membrane protein A (ompA) of R. anatipestifer . The eukaryotic expression plasmid carrying the fusion gene was transformed into Pichia pastoris ( P. pastoris ) to express the recombinant ompA and ompA–Fc proteins. Then, the effects of fused Fc on the vitality and antigen processing efficiency of duck peritoneal macrophages (PMø) were evaluated in vitro, whereas their immunogenicity was evaluated in vivo. Furthermore, Schisandra chinensis polysaccharide (SCP) was used to evaluate its immune-conditioning effects on the activation of PMø. SCP was also used as adjuvant to investigate immunomodulation on immunoresponses induced by the fused ompA-Fc in ducklings. The conventional Freund's incomplete adjuvant served as the control of SCP. Notably, ompA-Fc promoted phagocytosis of PMø and significantly increased serum antibody titers, CD4 + and CD8 + T-lymphocyte counts, lymphocyte transformation rate, and serum levels of IL-2 and IL-4. In addition, ducklings injected with the ompA-Fc vaccine exhibited considerably greater resistance to the R. anatipestifer challenge than those that received vaccines based on standalone ompA. Of note, SCP was demonstrated to boost the secretion of nitric oxide (NO), IL-1β, IL-6, TNF-α, and IFN-β by duck macrophages. In addition, the supplementation of SCP adjuvant to the ompA-Fc vaccines led to the further enhancement of immune response and vaccine protection. The dose of 200 μg/mL showed the most pronounced effects. This study provided valuable insights into protective strategies against R. anatipestifer infection. Highlights: This study demonstrated that the duck IgY Fc fragment could enhance the antigen processing efficiency of macrophages, leading to augmented antigen-induced immune response. Additionally, SCP as adjuvant showed excellent immunostimulatory effects on the ompA-Fc vaccine and can remarkably promote the activity of macrophages. Thus, SCP shows considerable potential in clinical applications, and SCP could be a good adjuvant choice for subunit vaccine. This study provided valuable insights into protective strategies against R. anatipestifer infection.